Proceso atención de enfermería en paciente de 29 años con tuberculosis pulmonar. - Gavilánez Lara, Lilian Maribel (2022)
Pulmonary tuberculosis is a chronic progressive bacterial infection that mainly affects the lungs, despite current treatments and prevention and control measures promoted by the Ministry of Public Health, it continues to be one of the main problems for Public Health, when detected the disease in time if it continues in a disciplined way with the established treatment, it will give us a favorable result for the patient and a speedy recovery. The reason why this clinical case study is carried out is that despite the daily efforts that are made at all levels of care, but especially at the primary health level, they have not been enough to eradicate Pulmonary Tuberculosis, since the incidence, prevalence and mortality rates continue to be maintained in our country and it is essential as future health professionals that we are prepared to face the different pathologies. The present work exposes detailed information of my 29-year-old patient diagnosed with Pulmonary Tuberculosis, the nursing care process is applied and a care plan and interventions focused on contributing care in individualized comprehensive care, emotional support with surveillance and periodic follow-ups are developed. to evaluate the evolution of health actions and thus be able to promote self-care of therapeutic management to my patient.